Effect of Surface Roughness on Aerodynamic Performance of Symmetric NACA 0012 - Hussein K. Mohammad (Tikrit Journal of Pure Science, 2025)
Roughness in a wind turbine blade surface has a large effect on its aerodynamic performance. The current research concentrates on the various effects of the surface roughness upon the aerodynamics of a symmetrical NACA 0012 airfoil. In this respect, six kinds of different grit sizes of sandpaper were used: P500, P1000, P1500, P2000, P2500, and P3000, to provide a range of roughened surfaces for the study. In this experiment, the lift and drag coefficients were measured at three angles of attack (5, 10, and 15 degrees), and at three flow speeds of (5, 10, and 15 m/s). It was realized that an increase in surface roughness significantly impairs the aerodynamic efficiency, depicted by a reduction in the lift coefficient and an augmenting coefficient of drag. These changes lead to a reduced lift-to-drag ratio and reflect the importance of smoothness of the surface of wind turbine blades to maintain optimal performance. Comparisons with previous studies corroborate these findings, proving that surface roughness generates increased turbulence and skin friction, causing deterrents in boundary layer development around the airfoil.